Preliminary studies on the development of IgA-loaded chitosan-dextran sulphate nanoparticles as a potential nasal delivery system for protein antigens. - Sharma, Sameer; Benson, Heather; Mukkur, Trilochan; Rigby, P.; Chen, Y. (Informa Healthcare, 2013)
This study describes the development of a biodegradable nanoparticulate system for the intranasal delivery of multiple proteins. Chitosan (CS)–dextran sulphate (DS) nanoparticles were developed and optimised for the incorporation of pertussis toxin (PTX) and a potential targeting ligand (immunoglobulin-A, IgA). In vitro characterization and in vivo uptake studies were performed for the evaluation of developed nanoparticles. The ratio of CS to DS, the order of mixing and pH of nanoparticle suspension were identified as important formulation factors governing the size and zeta potential of nanoparticles. An optimised CS–DS nanoparticle formulation prepared with the CS to DS weight ratio of 3 : 1 was used to load PTX and/or IgA. Entrapment efficiency of >90% was obtained for both. The in vivo uptake of IgA-loaded CS–DS nanoparticles in mice showed a preferential uptake of nanoparticles probably by nasal membranous or microfold cells following intranasal administration. The results of this study indicate the potential application of IgA-loaded CS–DS nanoparticles as a nasal vaccine delivery system.